2008
DOI: 10.1080/13651820802167136
|View full text |Cite
|
Sign up to set email alerts
|

Liver resection with bipolar radiofrequency device: Habib™ 4X

Abstract: Habib 4X is an additional device for hepatobiliary surgeons to perform liver resections with minimal blood loss and low morbidity and mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 30 publications
2
59
0
5
Order By: Relevance
“…Patients in the RF+ group required fewer blood transfusions (17.0% vs 24.1%), because small vessels in the section line that would ordinarily have bled in conventional hepatectomy were cauterized with RF waves and did not bleed during the liver resection. As in other works, RF-assisted liver resection was found to reduce the amount of intraoperative blood loss and the number of intraoperative blood transfusion procedures required effectively [13][14][15][16] . ALT and AST levels were measured on postoperative days to assess the extent of hepatocellular damage to the remaining liver.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Patients in the RF+ group required fewer blood transfusions (17.0% vs 24.1%), because small vessels in the section line that would ordinarily have bled in conventional hepatectomy were cauterized with RF waves and did not bleed during the liver resection. As in other works, RF-assisted liver resection was found to reduce the amount of intraoperative blood loss and the number of intraoperative blood transfusion procedures required effectively [13][14][15][16] . ALT and AST levels were measured on postoperative days to assess the extent of hepatocellular damage to the remaining liver.…”
Section: Discussionmentioning
confidence: 67%
“…The use of RFA devices to perform liver resection was described in 2002 by Weber et al [12] . Later, a bipolar, handheld disposable RFA device (HabibTM 4x) was developed especially for liver resection [13] . Then a series of studies by different groups confirmed the benefits of radiofrequency-assisted hepatectomy in reducing blood loss [16,17,24] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…В дальнейшем, по мере на-копления опыта, средняя цифра интраоперационной кровопотери возросла, в среднем до 305 мл, но все же нижняя ее граница осталась на прежнем, нулевом уровне, чего не отмечено при использовании ни одно-го инструмента применяемого в ходе диссекции тка-ни печени. Среднее время диссекции паренхимы при использовании аппарата составляет 45 мин, а общее время операции в среднем -205 мин [28].…”
Section: Discussionunclassified